Analysis of Strategy in Retaining Its Customers: A Case Study of Starbucks in Malaysia - Sekhar, Tushanthan A/L; Jian, Oh Zi; Liem, Gai Sin; Ying, Teoh Zhi; Sheng, Toh Kok; Xian, Tham Chui; Fitria, Yasmin Nur; Dewanti, Rosa Ayu; Thalib, Salsabilah Hani (The Global Academia Publisher, 2024)
Starbucks is an American coffee company and coffeehouse chain. The coffee chain in Malaysia is operated by Berjaya Starbucks Coffee Company Sendirian Berhad, which is part of the listed Berjaya Food Berhad. This study aims to analyze the strategy that Starbucks in Malaysia uses to retain its customers. The research methodology that we tend to use in this research is empirical as it will be conducted through primary data sources such as online survey techniques. The study will use questionnaires to gather information from Malaysian Starbucks customers. We want to do an empirical research paper because we are analyzing the strategy that Starbucks Malaysia is running to retain its customers as Starbucks is among the most well-known and recognized brands in the world. For that, we will analyze Starbucks' marketing formula and see how customers react to what Starbucks has done.